The Seven Sustainability Competences according to the RESFIA+D Model - Niko Roorda (The Central European Review of Economics and Management (CEREM), 2019)
Aim: The article describes the origins, structure and applications of a model for professional competences for sustainable development, called RESFIA+D. The model provides an assessment and policy instrument that can easily be applied practically.Companies, NGO's and other organizations may apply RESFIA+D as a structured tool for human resource development (HRD). Institutions for higher and vocational education can use the instrument for education (re)development, where curricula and didactic approaches are derived from a systematically designed competence profile in which sustainable development is integrated. Finally, individual professionals may use RESFIA+D as a tool for professional development.~Design / Research methods:The article defines the concepts of 'competence' and 'competent professionals', in an easily understandable style. Next, the structure of the RESFIA+D model is described. Scientific details, such as origins and validation, are described elsewhere; references are made to other sources.The basic set of RESFIA+D competences is combined with a structure of seven competence levels, which allows users to express the assessment results on an ordinal scale. This scale enables users to design plans for systematic improvements, both at a strategic and an operational level.~Conclusions / findings:As illustrated in the article, RESFIA+D was applied successfully within companies, universities, and by individual professionals.~Originality, value of the article:The article focuses in a unique way on the roles towards sustainability of individual professionals, whereas most or all usual assessment models focus on the roles of either entire organizations, or of individual persons seen as civilians or customers.
Keywords: 330; Competences; Sustainable Development; RESFIA D; Human Resource Development (HRD); Professionals; Organizations; Education